PERLINDUNGAN HUKUM JUSTICE COLLABORATOR PADA TINDAK PIDANA NARKOTIKA DI POLRESTA SIDOARJO - Abdillah, Moch. Fahmi; Sulistiyantoro, Hariyo (Gapenas Publisher, 2023)
In its implementation, the rules regarding justice collaborators are interpreted differently and appear to be trivialized by law enforcers, giving rise to uncertainty and the principle of legal certainty not being realized. This creates uncertainty and does not realize the principle of legal certainty, which in turn can affect the rights of justice collaborators. Violations of justice collaborators' rights can threaten their security. If violations like this continue to occur, the level of justice collaborators' trust in drug handling may decrease because they are reluctant and afraid to provide information to investigators. The SKB of the Minister of Law and Human Rights, the Attorney General, the Chief of Police, the Corruption Eradication Commission and the Chair of the LPSK was formed to avoid overlapping regulations in determining legal protection for perpetrators who become justice collaborators. However, the different perspectives of law enforcers regarding cooperating actors are what makes it difficult to obtain the rights of cooperating Justice Collaborators. This is also caused by a lack of understanding of the regulations regarding actors working together. So that opens up a gap for different views. One of the inhibiting factors in the implementation of providing protection for Justice Collaborators so far. The SKB of the Minister of Law and Human Rights, the Attorney General, the Chief of Police, the Corruption Eradication Commission and the Chair of the LPSK was formed to avoid overlapping regulations in determining legal protection for perpetrators who become justice collaborators. However, the different perspectives of law enforcers regarding cooperating actors are what makes it difficult to obtain the rights of cooperating Justice Collaborators. This is also caused by a lack of understanding of the regulations regarding actors working together. So that opens up a gap for different views. One of the inhibiting factors in the implementation of providing protection for Justice Collaborators so far